Effect of limit-fed, high energy growing rations on the performance of feedlot steers - Goldy, G.; Downey, B.; Bolsen, K.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Steers red high-concentrate limit-fed rations were more efficient during growing than steers fed silage plus grain at 25% of their dry matter (DM) intake, or silage only. The limit-fed cattle also tended to gain faster (P<.10) and were more efficient (P<.05) during the finishing phase and did not have the expected depressed DM intakes compared to cattle fed the other growing-phase rations. Steers fed barely had lower DM intakes (P<.05) but gained more efficiently (P<.05) than those fed grain sorghum.
Keywords: Beef; Feedlot; Steers; High energy rations